If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3y + 2z = -5 Solving 2x + -3y + 2z = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 2x + -3y + 3y + 2z = -5 + 3y Combine like terms: -3y + 3y = 0 2x + 0 + 2z = -5 + 3y 2x + 2z = -5 + 3y Add '-2z' to each side of the equation. 2x + 2z + -2z = -5 + 3y + -2z Combine like terms: 2z + -2z = 0 2x + 0 = -5 + 3y + -2z 2x = -5 + 3y + -2z Divide each side by '2'. x = -2.5 + 1.5y + -1z Simplifying x = -2.5 + 1.5y + -1z
| 0=-16x^2-16x+160 | | x-291=-8x-3 | | 17x-23=8y-12 | | -7=a/-19 | | -5/y=-10 | | 3d+8=11 | | 39x+19=100 | | -22=a/6 | | G(-1)=xsquared+1 | | 0=-16x^2+160x+32 | | 4/9×1/8 | | W=G+Grt | | M/23=-16 | | -11.25t+5=14 | | -4b+(-9k)-6-3b+12= | | M/18=-17 | | 3g+9+2g+5=50 | | 2+5x-8=2x-4+x | | H(20)=10 | | 232/36= | | 10/y=50 | | 4v+4=5+1v | | 3(16)-48+8= | | 4-6x=8x+18 | | 5x-6y+3z=-9 | | 8+6(-3x+4)= | | 4=-8+2x | | 3(2x-1)-4=29 | | 13-x/3=17 | | -x-3=x+95 | | -7m+2=-75 | | 1k^2-11k+30=0 |